Association of Hemoglobin Decrement During Hospitalization with Prognosis of Aneurysmal Subarachnoid Hemorrhage and Mediation Effects of Cerebral Infarction and Pneumonia - Che X; Wu B; Zhang H; Jiang D; Fu W; He Z (International Journal of General Medicine)
Xudong Che, Baixue Wu, Hongxia Zhang, Dengzhi Jiang, Wenqiao Fu, Zhaohui He Department of Neurosurgery, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Zhaohui He, Email geno_he@163.comBackground: Hemoglobin decrement is a common complication after aneurysmal subarachnoid hemorrhage (aSAH) and is associated with poor outcome. However, the mediating variables on the causal pathway between hemoglobin decrement and poor outcome in aSAH are not clear.Methods: This is a single-center retrospective observational study containing all consecutive patients with aSAH admitted to our hospital between January 1, 2019, and June 30, 2022. Hemoglobin decrement was defined as the hemoglobin at admission minus the minimum hemoglobin during hospitalization. Calculation of cutoff value using ROC curve Youden index. The main exposure of interest was a hemoglobin decrement greater than the cutoff value. The primary outcome was poor outcome at 3 months (mRS 4– 6).Results: A total of 480 patients with aSAH were included in the study, 414 (71.1%) had a favorable and 66 (28.9%) had a poor outcome at 3 months. The cut-off value for calculating the degree of hemoglobin decrease using the ROC curve was 12.5 g/l. Hemoglobin decrement greater than the cutoff value was significantly associated with pneumonia (OR 3.12; 95% CI 1.78– 5.57; p < 0.001), cerebral infarction (OR 3.06; 95% CI 1.80– 5.30; p < 0.001), and poor prognosis (OR 2.88; 95% CI 1.44– 5.92; p = 0.003) at 3 months. The mediation effect was significant for both pneumonia and cerebral infarction, with the average causal mediation effect (ACME) were 0.04 (95% CI 0.02– 0.08; p < 0.05) and 0.05 (95% CI 0.02– 0.08; p < 0.001), respectively.Conclusion: Hemoglobin decrement during hospitalization was significantly associated with poor prognosis after aSAH, and the increased risk of cerebral infarction and pneumonia might mediate this effect. Avoiding hemoglobin decrement greater than 12.5g/l may improve the prognosis of patients with aSAH.Keywords: aneurysmal subarachnoid hemorrhage, hemoglobin decrement, cerebral infarction, pneumonia